2021
DOI: 10.1007/s00228-021-03101-4
|View full text |Cite
|
Sign up to set email alerts
|

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers

Abstract: Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Previous research shows that these resources can be effective in teaching the knowledge, skills and attitudes required for safe, effective and responsible prescribing 5 . A large variety of online problem-based resources is already being used for CPT training in universities throughout Europe, but while teachers reported that they are willing to share these materials, they currently rarely do so 6,7 . Actively sharing these materials will aid local teachers to improve their CPT curricula by making them more problem-based.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research shows that these resources can be effective in teaching the knowledge, skills and attitudes required for safe, effective and responsible prescribing 5 . A large variety of online problem-based resources is already being used for CPT training in universities throughout Europe, but while teachers reported that they are willing to share these materials, they currently rarely do so 6,7 . Actively sharing these materials will aid local teachers to improve their CPT curricula by making them more problem-based.…”
Section: Introductionmentioning
confidence: 99%
“…Actively sharing these materials will aid local teachers to improve their CPT curricula by making them more problem-based. Moreover, the platform will allow teachers to be inspired, share teaching experiences and collaborate on new international teaching resources 6 . In light of the recent COVID-19 pandemicwhich forced educators to abruptly adopt online teaching methods-the need for high-quality online teaching resources is high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aimed at improving and harmonizing international CPT education, EurOP 2 E is an online environment for CPT teachers to collaborate and to share and create open educational resources. The framework for the platform was recently published, 6 and it is set to go live in the spring of 2022 (www.prescribingeducation.eu).…”
mentioning
confidence: 99%
“…Aimed at improving and harmonizing international CPT education, EurOP 2 E is an online environment for CPT teachers to collaborate and to share and create open educational resources. The framework for the platform was recently published [7], and it is set to go live in early 2022. Alike the call to action towards the NHS, we hereby make an appeal for teachers in CPT to join the EurOP 2 E network, and for those who are invested in sustainable prescribing to collaboratively create open educational resources about this (www.prescribingeducation.eu).…”
mentioning
confidence: 99%